(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: Determining the species of malaria vector Anopheles and the rate of Plasmodium spp. infection in Anopheles in four Central Highlands provinces by using molecular biology techniques. Methods: Mosquitoes were morphologically classified according to the National Institute of Malariology, Parasitology, and Entomology classification chart (2008). Species identification was performed using PCR, while the presence of Plasmodium spp. within the mosquitoes was detected using ddPCR targeting the 18S rRNA gene region. Results: In Kon Tum, a total of 13 Anopheles species were collected, including two primary malaria vectors (An. dirus and An. minimus) and two secondary vectors (An. aconitus and An. maculatus). In Gia Lai, 14 species of Anopheles were collected, comprising one primary vector (An. minimus) and two secondary vectors. Similarly, 13 species were identified in Đak Lak, including An. dirus and two secondary vectors. In Dak Nong, 12 species were documented, consisting of two primary vectors and two secondary vectors. The primary vectors were predominantly collected using cattle-baited traps, with additional methods including bed nets, indoor light traps, and cattle light traps. Of the 694 An. minimus and An. dirus mosquito samples collected across the four provinces, 6 samples (0.86%) were positive for Plasmodium spp. In Kon Tum, 3 out of 196 samples (2.8%) were positive, while in Gia Lai, 3 out of 190 samples (1.58%) were positive. All positive samples were identified as An. minimus. Conclusion: The study confirmed the presence of primary malaria vectors (An. dirus and An. minimus) and secondary vectors in four Central Highlands provinces. The ddPCR technique successfully detected Plasmodium spp. in a small proportion of mosquito samples, predominantly in An. minimus. Ongoing surveillance and control of primary vectors are essential to mitigate the risk of malaria transmission in this region, particularly as mosquito species continue to adapt and exhibit changes in behavior